(untitled) (American Journal of Islam and Society, 1991)
Ever since its revelation more than fourteen hundred years ago, the Qur’an has been the object of recitation and memorization, as well as scholarly analysis by millions in every generation. During this long span of time, not only religious scholars and jurists, but also other professionals like physicists, medical doctors, historians, and orientalists have tried to scrutinize and analyze the Qur’an. It is about time that sociologists paid attention to this primary source of Islam. Sociological interest in the Qur’an, as belated as it is, is in fact natural, for, after a brief foray in the direction of what one may call Origin IheoZogy, the basic thrust of the Qur’an remains ideological- humanity and its society in this world. Not that this is such a revealing idea. Whether one looks at it from a juristic point of view or from a historical perspective, it hardly escapes notice that the Qur’anic verses speak out loudly about the nature of plural living as fabricated by the crisscrossing episodes generated by very active, assertive, and expressive individuals over the course of history. Most of what has been going on in Islamic studies, under the rubric of law and history in particular, provides us with sufficient encouragement to cast a fresh look at the same source of knowledge. Questions Sociological Theory Should Answer As we have already seen, sociologists have at different times asked different and disparate, although quite relevant, questions. They have also been insufficient questions. For example, symbolic interactionists remained interested primarily in the indeterminstic nature of the human act. This microscopic preoccupation prevented them from asking questions about social processes of a larger magnitude. Even Blumer’s emphasis on collective behavior, which showed an early promise for the analysis of revolutionary social change, has had only scant appeal for his fellow symbolic interactionists. On the other hand, structural-functionalists as well as conflict theorists remained interested in the deterministic nature of the macro social order ...